Smelly Fumes: Volatile-Mediated Communication between Bacteria and Other Organisms - Paolina Garbeva (Frontiers Research Topics, 2017)
This e-book summarizes recent advances in the young and rapidly developing field of microbial volatiles. Articles included here reveal novel information about the chemical diversity of bacterial and fungal volatiles, their functions, their roles in inter-specific and inter-kingdom interactions and the metabolic and physiological changes their exposure causes in the target organisms. The e-book is divided in three chapters: (1) Natural Functions of Microbial Volatiles; (2) Volatile Production and Ecosystem Functioning and (3) Volatile Detection and Identification.